Discovery of ammonoid jaw apparatus and associated features using reflectance transformation imaging (RTI) - Moron Alfonso, Daniel Andres; Cichowolski, Marcela; Hoffmann, René; Rodriguez, Maricel Gabriela (Publicación Electrónica de la Asociación Paleontológica Argentina)
We report on remains of the buccal apparatus and possible associated structures for the Late Cretaceous ammonite Maorites seymourianus from the Lopez de Bertodano Formation (Antarctic Peninsula). This is the first description of these structures for the family Kossmaticeratidae. Further, we discuss the most likely taphonomic processes taking place that allowed this exceptional preservation. Reflectance Transformation Imaging (RTI) technique was employed in this work to better document the faint structures. We briefly provide a review of this method and its potential importance for paleontological studies because it seems that this powerful technique has been largely overlooked by paleontologists. En este trabajo se reporta la presencia de elementos del aparato bucal y posibles estructuras asociadas en un amonite de la especie Maorites seymourianus de la Formación López de Bertodano (Cretácico Tardío, Península Antártica), y se discuten los procesos tafonómicos que habrían permitido esta preservación excepcional. Esta es la primera descripción de estas estructuras para la familia Kossmaticeratidae. Para este estudio se empleó una técnica denominada Reflectance Transformation Imaging (RTI) relativamente poco aplicada en estudios paleontológicos, por lo que se provee una breve revisión del método y se indica su potencial importancia para estos estudios. Fil: Moron Alfonso, Daniel Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Cichowolski, Marcela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; ...